The Effectiveness of Social Protection Programs in Alleviating Poverty in Bangladesh: A Systematic Review - Aryabhatta Chakarvarti (Journal of Public Representative and Society Provision, 2022)
To what extent have social protection initiatives in Bangladesh been successful in reducing poverty? Our search of academic databases yielded a total of 10 studies that fulfilled our requirements for inclusion. Our research shows that social security programs like government-funded cash handouts, medical coverage, and food stamps have helped reduce poverty in rural Bangladesh. The results of this analysis will shed light on the efficacy of Bangladesh's social protection programs and guide future policy decisions for strengthening their implementation and influence. However, problems with program execution and maintenance continue to be an issue. Our analysis emphasizes the significance of improving program design and execution to reach the most vulnerable populations in Bangladesh, as well as the need for additional research on the long-term effect and sustainability of social security programs in that country.